La producción de cuy y las ventas en el cantón Cevallos provincia de Tungurahua, período 2017 - Karla Alejandra, Sánchez Lascano (2018)
The present investigation analyzes the production of guinea pigs and the sales in the Cevallos Canton for which it has been proposed as objectives to diagnose if the sale of this product benefits the local market, establish the forms of commercialization used and boost the productivity and commercialization of the guinea pig With this, the research will be able to identify how the production of guinea pig affects the level of sales of the producers. In addition, the production of guinea pigs is important because the greater the production of guinea pigs, the greater the chances that there will be an increase in sales and for this it is necessary to keep a greater number of breeding guinea pigs. The commercialization of guinea pigs in the Cevallos canton is an important economic source since this helps to improve its development. On the other hand, a methodology has been used where field research, documentary, the instrument and technique used are the survey that has a questionnaire that allows gathering information on the subject of analysis. Finally, for the processing of the results we used a statistical tool SPSS that allowed us not only to generate graphs and tables but also to check the hypothesis.